FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI KELURAHAN AIR HITAM PEKANBARU - fatmaricha rahmana; Hidayati Lestari (Jurnal Ilmu Kebidanan, 2020)
Mother's knowledge has a significant effect on birth weight. With sufficient nutritional knowledge, it is hoped that someone can change behavior for the better condition, so that mothers can choose nutritious food ingredients and compile a balanced menu according to their needs and tastes. Therefore, through good knowledge about nutrition during pregnancy, it is hoped that mothers can plan programs healthy pregnancy, and will give birth to a baby with normal weight (≥2500 grams). The purpose of this study was to determine the relationship between the level of knowledge of post-partum mothers about maternal nutrition during pregnancy with the weight of the baby she was born with. This research is an analytical study with a cross sectional research design. The technique used in sampling is accidental sampling with a total sample of 32 postpartum mothers in Camar I Room Arifin Achmad Hospital, Riau Province, the tools used in sampling are questionnaires, and analyzed by univariate and bivariate using the chi square statistical test formula. The results of the univariate analysis were 23 people (71.9%) mothers who had high knowledge of pregnant women nutrition, and 27 people (84.3%) mothers who had babies with normal birth weight (≥ 2500 grams). From the results of the calculation of the chi square statistical test, it is obtained x² count 5.1 and x² table 2.70. Furthermore, it is compared between calculated x² and x² table, namely 5.1> 2.70. So the results of the chi square statistical test showed that there was a significant relationship between the mother's knowledge of nutrition during pregnancy and the birth weight of the baby. Suggestions are given to related parties, in this case the hospital, to continuously strive to increase maternal knowledge about health in general and maternal nutrition during pregnancy, especially through health promotion efforts.